NILAI TAMBAH DAN KEBERLANJUTAN USAHA PENGOLAHAN PISANG DI KECAMATAN CURUP TENGAH KABUPATEN REJANG LEBONG (STUDI KASUS PISANG SARI GIZI KAMISO KARTO) - Utami, Atin; Utama, Satria Putra; Asriani, Putri Suci (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2020)
The objective of the research were to : (1) calculate and analyze the value added generated from the banana processing bussiness Sari Gizi Kamiso Karto in Curup Tengah Sub-District of Rejang Lebong Regency, (2) know and analyze the sustainability level of banana processing Bussiness Sari Gizi Kamiso Karto in Curup Tengah SubDistrict Of Rejang Lebong Regency. The research were used primary data and secondary data. Data analysis included value added analysis with Hayami Method, to determine the sustainability of the bussiness conducted a descriptive study that can be seen from the ratio of added value, labor market and profit levels. The results showed that : (1) the amount of value added obtained from the production of banana ambon into pisang sale and pisang kepok became banana chips that were equal to Rp 37.625,52/kg and Rp.27.877,24/kg (2) based on calculations using Hayami Method by looking the indicators of bussiness sustainability on banana sale products and banana chips has a high level of bussiness sustainability.